Analysis of the Influence of Financial Literacy and Financial Attitudes on the Use of Electronic Payment Systems - Henrikus Friandi Khristian; Sumilir Sumilir; Yudi Nur Supriadi (Garuda Prestasi Nusantara Consulting, 2024)
This study is a quantitative research that aims to analyze the influence of financial literacy and financial attitudes on the use of electronic payment systems. In this study, active students of the Management study program of the Veteran National Development University of Jakarta in the 2023 academic year were used as the population and a sample of 100 respondents was taken using random sampling techniques. Data was collected by distributing questionnaires through google forms. The data analysis technique used is the Partial Least Square (PLS) analysis method with Smart PLS 4.0 software. The results of the study show that financial literacy has an effect on the use of electronic payment systems and financial attitudes have an effect on the use of electronic payment systems. Keywords: Financial Literacy, Financial Attitude, Electronic Payment System